2022
DOI: 10.1155/2022/9348917
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant ARMCX1 Expression Is an Independent Predictor of Poor Prognosis in Gastric Cancer

Abstract: ARMCX1 (Armadillo repeat containing X-linked 1) is identified to be the novel tumor suppressor gene related to multiple tumor types. Nonetheless, its effect on gastric cancer (GC) is still poorly understood. The present work determined ARMCX1 level within GC and the relation with clinicopathological characteristics. This work also collected relevant information in The Cancer Genome Atlas (TCGA) database for investigating associations of ARMCX1 with clinicopathologic variables and then validated in our GC cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…Our results suggest that the poor prognosis of GC and CCA is related to the overexpression of APBB1 , ARMCX1 , DZIP1 , and MSRB3 . Our results of the functional enrichment analysis of the GC and CCA genes are consistent with previous reports ( 13 , 14 ). The metabolism of cancer cells plays an important role in the occurrence and development of tumors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results suggest that the poor prognosis of GC and CCA is related to the overexpression of APBB1 , ARMCX1 , DZIP1 , and MSRB3 . Our results of the functional enrichment analysis of the GC and CCA genes are consistent with previous reports ( 13 , 14 ). The metabolism of cancer cells plays an important role in the occurrence and development of tumors.…”
Section: Discussionsupporting
confidence: 93%
“…We found that 4 hub genes (i.e., APBB1 , ARMCX1 , DZIP1 and MSRB3 ) were closely related to the OS rate of GC patients. ARMCX1 has been reported to have potential prognostic value for GC and may have clinical application value ( 13 ). However, further basic research needs to be conducted to clarify the specific mechanism of ARMCX1 in GC.…”
Section: Discussionmentioning
confidence: 99%
“…The genes that demonstrated the strongest negative correlation with viral load ( Supplementary Table 2 ) also have key functional overlaps. For example, PTPN13, SFMBT1, ARMCX1, ZNF10, and ZBTB18 are all involved in repression of transcription ( Huang et al., 2008 ; Nishitsuji et al., 2015 ; Liu et al., 2020 ; Heng et al., 2022 ; Xie et al., 2022 ). Downregulation of ZNF10 during high viremia is noteworthy as this protein has demonstrated functional capacity to limit HIV-1 gene expression in vitro ( Nishitsuji et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above background, we perform our study. Studies showed that the ARMCX gene family plays a vital role in gastric cancer (GC) and is a potential prognostic biomarker 22,23 . Kurochkin IV, et al deem that ALEX genes, ARMCX, also known as ALEX, play a role in the suppression of cancer progression 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The hypermethylation of ARMCX1 was found in ovarian cancer 37 . ARMCX1 is a prognostic factor of GC 23 . Thus, we use two online databases to complete the methylation analysis in PAAD.…”
Section: Discussionmentioning
confidence: 99%